2017
DOI: 10.4187/respcare.05264
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Initial Response to High-Frequency Jet Ventilation in Premature Infants With Hypercapnic Respiratory Failure

Abstract: BACKGROUND: High-frequency jet ventilation (HFJV) has been used in conjunction with conventional ventilation for infants with respiratory failure. We sought to identify parameters that were associated with successful application of HFJV in patients with hypercapnic respiratory failure. METHODS: A single-center, retrospective review of infants who received HFJV was conducted. Subjects were enrolled if birthweight was <2,000 g and capillary P CO 2 was >55 mm Hg. Ventilator parameters and physiologic data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…OSI (ie, mean airway pressure  F IO 2  100/S pO 2 ) has a strong linear correlation with the oxygen index and had been validated as a noninvasive method for assessing the severity of respiratory illness in infants and children. [26][27][28] Recently, Muniraman et al 29 demonstrated that the oxygen index derived from OSI was strongly correlated (r ¼ 0.89) and may provide reliable assessment of respiratory failure on a 12 Collectively, these findings suggest that OSI is a useful metric for guiding interventions, evaluating treatment response, and identifying risk stratification in premature infants, and our results support these findings. Our data suggest that ductal patency confers a survival benefit because subjects who did not have a patent ductus arteriosus demonstrated a nearly 8-fold increase in mortality.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…OSI (ie, mean airway pressure  F IO 2  100/S pO 2 ) has a strong linear correlation with the oxygen index and had been validated as a noninvasive method for assessing the severity of respiratory illness in infants and children. [26][27][28] Recently, Muniraman et al 29 demonstrated that the oxygen index derived from OSI was strongly correlated (r ¼ 0.89) and may provide reliable assessment of respiratory failure on a 12 Collectively, these findings suggest that OSI is a useful metric for guiding interventions, evaluating treatment response, and identifying risk stratification in premature infants, and our results support these findings. Our data suggest that ductal patency confers a survival benefit because subjects who did not have a patent ductus arteriosus demonstrated a nearly 8-fold increase in mortality.…”
Section: Discussionsupporting
confidence: 81%
“…Subjects were converted to HFJV in accordance with institutional guidelines, which have been described in a previous publication and are highlighted in Figure 1. 12 HFJV peak inspiratory pressure was primarily adjusted to maintain a pH $ 7.25 and capillary P CO 2 of 45-60 mm Hg. F IO 2 was titrated to maintain S pO 2 between 88% and 94%.…”
Section: Subjectsmentioning
confidence: 99%
“…Severe refractory respiratory failure was de ned when patients with a PaO 2 /FiO 2 ratio under 150 on two consecutive arterial blood gas (ABG) samples and/or had an initial oxygenation index (OI) ≥ 20 [21]. Poor response to conventional ventilation was de ned as failure to decrease PCO 2 > 10% and/or FiO 2 > 20% after 1 hour treatment by conventional ventilation (CV) at maximal settings [22,23]. Exclusion criteria were patients < 24 weeks of gestation, incomplete medical records, and patients with severe congenital anomalies (ex.…”
Section: Study Design Settings and Patientsmentioning
confidence: 99%
“…Current evidence does not allow recommendations for using HFJV routinely in preterm infants with respiratory distress syndrome, and its use is very restricted. 10 In a 4-y retrospective study, Wheeler et al 11 sought to identify measurable physiological factors to predict the successful use of HFJV as a rescue ventilation mode in subjects with acute hypercapnic respiratory failure. Lower gestational age, the use of lower peak inspiratory pressure in the previous conventional mechanical ventilation, reduction in F IO 2 and in capillary P CO 2 , and improvement in pH during the first hour of HFJV were predictors of better outcome.…”
mentioning
confidence: 99%
“…Increases in the oxygen saturation index and F IO 2 in 4 h were associated with worse outcome to HFJV. According to the study by Wheeler et al, 11 an increase in the oxygen saturation index within 4 h under HFJV might be an indicator of the need for changes in the ventilation strategy, through either an increase in PEEP, an increase in mean airway pressure, or an unnecessary extension of the period of use of HFJV.…”
mentioning
confidence: 99%